Thrifting dalam Perspektif Fikih Prioritas - Nurbaiti Bahrudin; Munawir Sajali; Sri Pramudya Wardhani; Lili Hastuti (Journal of Law, Society, and Islamic Civilization, 2024)
Thrifting is growing in Indonesia in in recent years. Thrifting is often seen as a solution to reduce waste, especially textile waste. Thrifting that is mostly done in Indonesia is thrifting which is done by importing used clothes. Meanwhile, UMKM textiles in Indonesia are declining. The method in this study uses qualitative research. A method that describes in depth about thrifting from various literatures. Then analyzed using the priority fiqh approach (fiqh al-aulawiyyat) reformulated by Jasser Auda. examine in depth the factors and their impact. Both everything that creates damage personally and damage in general. This is to serve as a guide to determine the level of urgency of thrifting for the public. The conclusion of this study is that thrifting is shopping for used goods with the aim of getting cheaper prices for both local and imported goods. Thrifting which is mostly done by the people of Indonesia today is on imported goods. Thus, thrifting activities have a position that does not have to be prioritized. On the contrary, if thrifting is carried out on local goods or products, then thrifting has a position that must be prioritized.